Single dc-source-based seven-level boost inverter for electric vehicle application - Pilli N.K.; Raghuram M.; Kumar A.; Singh S.K. (My University, 2025)
This study offers an effective circuit arrangement of a multilevel inverter that can increase the number of output voltage levels with a lesser number of device count. A single dc-source-based seven-level inverter (LI) with boosting capability is proposed in this study. The proposed inverter utilises eight switches, two diodes, two capacitors, one inductor and a single dc source to generate seven-level boosted output. Usage of single dc source and boosting capability makes the proposed inverter suitable for electric vehicles as less number of series-connected battery cells are required. Phase-shifted pulse-width modulation (PWM), a multi-carrier-based PWM technique is utilised to generate switching pulses for the proposed 7LI. Device count-based comparative analysis of the proposed inverter with recent topologies is done. Viability and impact of the proposed inverter are analysed through simulation and are validated through laboratory prototype. © The Institution of Engineering and Technology 2019.